Learning on Jupiter, learning on the Moon: the dark side of the G-force. Effects of gravity changes on neurovascular unit and modulation of learning and memory - Porte, Yves; MOREL, Jean-luc (Frontiers in Behavioral Neuroscience, 2012)
On earth, gravity vector conditions the development of all living beings by physically imposing an axis along which to build their organism. Thus, during their whole life, they have to fight against this force not only to maintain their architectural organisation but also to coordinate the communication between organs and keep their physiology in a balanced steady-state. In space, astronauts show physiological, psychological, and cognitive deregulations, ranging from bone decalcification or decrease of musculature, to depressive-like disorders and spatial disorientation. Nonetheless, they are confronted to a great amount of physical changes in their environment such as solar radiations, loss of light-dark cycle, lack of spatial landmarks, confinement and obviously a dramatic decrease of gravity force. It is thus very hard to selectively discriminate the strict role of gravity level alterations on physiological, and particularly cerebral, dysfunction. To this purpose, it is important to design autonomous models and apparatuses for behavioural phenotyping utilisable under modified gravity environments. Our team actually aims at working on this area of research.